The Dissemination and Development of Chinese Medicine in Pakistan - Jie LIN; Saeed Saboor; Jin LU (Wolters Kluwer Health/LWW, 2024)
Abstract. The article focuses on the dissemination and development of Chinese medicine in Pakistan. Religious records show that Chinese medicine was introduced to Pakistan as early as 1,400 years ago, while Hijama (Chinese cupping) was used by Prophet Hazrat Muhammad to cure different types of diseases. Exchanges and cooperations between China and Pakistan continue to the present day. Acupuncture and moxibustion therapy, cupping therapy and herbal medicine are practiced with significant merits in today's Pakistan. In the future, with the proposal of the Belt and Road Initiative and the landmark project of China-Pakistan Economic Corridor, Chinese medicine can be strengthened through cooperations at the herbal medicine trade level, the research and development level, the educational level, and the social association level.